THE SOPHOMORES’ PERSPECTIVE ON ENGAGING TED-Ed WEBSITE IN ENHANCING SOPHOMORES’ VOCABULARY MASTERY - Sri Asti Ramdhani; Asiyah Mumtahanah Khoiruzzahra (JALL (Journal of Applied Linguistics and Literacy), 2018)
TED-Ed (Technology,  Entertainment, Design,-Education) is an educational and initiative website for youth that can be used by teachers or lecturers to spark and celebrate the ideas to teach the sophomores around the world. The study is aimed at investigating the sophomores’ perspective toward vocabulary learning activities through TED-Ed website. In this study, the writers addressed to two research questions: 1. What benefits do the sophomores gain from the use of TED-Ed website? 2. What obstacles do the sophomores gain from the use of TED- Ed website? To obtain the data, the writers employed a qualitative metodology under a cross- sectional survey technique. Under this technique, the writers administered the questionnaire to 20 sophomores. The results of the first research question showed that 40% of the respondents answered that TED-Ed Website can improve vocabulary mastery, 40% of the respondents asserted that TED-Ed Website helps the sophomores to understand the material. Meanwhile, 20% of the respondents stated that TED-Ed Website can make the lesson fun. The results of the second research question asserted that 60% of the respondents claimed that they found the obstacle because of the unsupported facilities, whereas 20% of the respondents answered  that  there is  no  abstacle on  engaging to  TED-Ed  Website to  have the video. Furthermore, 15% of the respondents claimed that the video sometimes do not suit for the materials, and 5% of the respondent purposed that they could not understand each word from the videos. To sum up, the most of respondents perceived that TED-Ed website is very useful for them. Besides, the most of the respondents perceived that they have obstacles in learning vocabulary through the videos fromTED-Ed website. Keywords: The Sophomores’ Perspective, Vocabulary Learning, TED-Ed website